Association between Metabolic Syndrome and the Severity of Ischemic Heart Disease: Metabolic Syndrome and Ischemic Severity - Javaid, Saad; Anwar, Awais; Shaikh, Imran Ali; Sajad, Qamar; Khan, Fahad Aman; Iqbal, Muhammad Hasnain; Shuja, Mamoona (Pakistan Journal of Health Sciences, 2024)
Ischemic Heart Disease (IHD) was a leading cause of mortality worldwide, often complicated by metabolic syndrome, which includes hypertension, hyperglycemia, and dyslipidemia. Objective: To investigate the association between metabolic syndrome and the severity of ischemic heart disease. Methods: Data were collected from the cohort’s existing records, including clinical assessments, laboratory tests, and self-reported questionnaires. Metabolic syndrome components were evaluated using the National Cholesterol Education Program Adult Treatment Panel III (NCEP ATP III) criteria. Participants were classified as having metabolic syndrome if they met three or more of the following criteria: abdominal obesity, elevated blood pressure, elevated fasting glucose, high triglycerides, and low HDL cholesterol. IHD incidence was determined through medical records, hospital admissions, and mortality data, defined as non-fatal myocardial infarction, unstable angina, or coronary revascularization. Statistical analysis included calculating the incidence rate of IHD for participants with and without metabolic syndrome, expressed as IHD cases per 1,000 person-years. Cox proportional hazards regression models were used to assess the association between metabolic syndrome and IHD incidence, adjusting for confounders such as age, sex, smoking status, physical activity, and family history of cardiovascular disease. Hazard Ratios (HRs) with 95% Confidence Intervals (CIs) were reported. Results: The incidence of IHD was significantly higher in participants with metabolic syndrome. Cox regression showed metabolic syndrome was associated with increased IHD incidence (HR: 2.70, 95% CI: 1.50–4.80, p < 0.001). Conclusion: Metabolic syndrome was significantly associated with IHD incidence. Early identification and management were essential to reduce IHD risk.